Assessing the Governance Context Support for Creating a Pluvial Flood Risk Map with Climate Change Scenarios: The Flemish Subnational Case - Cesar Casiano Flores; Joep Crompvoets (ISPRS International Journal of Geo-Information, 2020)
Climate change has increased pluvial flood risks in cities around the world. To mitigate floods, pluvial risk maps with climate change scenarios have been developed to help major urban areas adapt to a changing climate. In some cases, subnational governments have played a key role to develop these maps. However, governance research about the role of subnational governments in geospatial data development in urban water transitions has received little attention. To address this gap, this research applies the Governance Assessment Tool as an evaluative framework to increase our understanding of the governance factors that support the development of pluvial flood risk maps at the subnational level. For this research, we selected the region of Flanders in Belgium. This region is considered among the frontrunners when it comes to the creation of a pluvial flood risk map with climate change scenarios. Data have been collected through in-depth interviews with steering committee actors involved in the development process of the map. The research identified that the current governance context is supportive of the creation of the flood risk map. The government of Flanders plays a key role in this process. The most supportive qualities of the governance context are those related to the degree of fragmentation (extent and coherence), while the less supportive ones are those related to the “quest for control” (flexibility and intensity). Under this governance context, government actors play the primary role. The Flemish government led the maps’ creation process and it was supported by the lower governmental levels. As the provincial government was an important actor to increase local participation, collaboration with private and non-governmental actors in the steering committee was more limited. The financial resources were also limited and the process required a continuous development of trust. Yet, the Flemish Environmental Agency, with the use of technology, was able to increase such trust during the process.